Targeted Metabolomics Using LC‐MS in Neurospora crassa. Issue 5 (26th May 2022) - Carrillo, Alexander J.; Halilovic, Lida; Hur, Manhoi; Kirkwood, Jay S.; Borkovich, Katherine A.
Abstract: The filamentous fungus Neurospora crassa has historically been a model for understanding the relationship between genes and metabolism—auxotrophic mutants of N. crassa were used by Beadle and Tatum to develop the one‐gene‐one‐enzyme hypothesis for which they earned the Nobel Prize in 1958. In the ensuing decades, several techniques have been developed for the systematic analysis of metabolites in N. crassa and other fungi. Untargeted and targeted approaches have been used, with a focus on secondary metabolites over primary metabolism. Here, we describe a pipeline for sample preparation, metabolite extraction, Liquid Chromatography‐Mass Spectrometry (LC‐MS), and data analysis that can be used for targeted metabolomics of primary metabolites in N. crassa . Liquid cultures are grown with shaking in a defined minimal medium and then collected using filtration. Samples are lyophilized for 2 days at –80°C, pulverized, and mixed with a solution to extract polar metabolites. The metabolites are separated and identified using LC‐MS, with downstream analysis using Skyline interpretive software. Relative levels of hundreds of metabolites can be detected and compared across strains. © 2022 Wiley Periodicals LLC. Basic Protocol : Metabolite extraction and detection from Neurospora crassa cell cultures using Liquid Chromatography‐Mass Spectrometry